ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PADA MATERI POLA BILANGAN DITINJAU DARI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP AHMAD DAHLAN METRO - Budi Santoso; Lena Wahyuni; Nur Rahmah Lutfiah; Ma’rifatun Nikmah; Miftah Qurrahman Mu’afii (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
The purpose of this study is to analyze students' mistakes in solving problems in the material number patterns. In this study, researchers used a quantitative descriptive method. Data collection techniques in this study were carried out through several stages, namely: Observation and Test. Researchers used the test in the form of essay questions as many as 4 items related to material number patterns by emphasizing the students' mathematical communication skills. Where the indicator of the problem is students are able to express opinions and state the situation there are questions number 1 parts a and b, state the situation, pictures, diagrams, or real objects into language, symbols, ideas or models number 2 parts c and d. From the indicators above the researcher determines the assessment instrument, where the researcher uses the guidelines Research methods based on the philosophy of postpositivist, this method is used to examine the condition of natural objects such as student communication skills, as a research instrument this sampling uses categories with levels of student mathematical communication skills, then selected 3 levels of student abilities are: high, medium, and low ability with the provisions of low <40, medium 40-70 and high> 70. The researcher can conclude that know the percentage of the average student answer error in each question is 48, 3% in problem 1a and get the same result in Problem 1b is 48.3%, then the lowest result in Problem 2c is 13.3% and Problem 2d is 26.6%, it can be concluded that the average error of students in answering the whole essay item is 34% or it can be said to be low where the students' mistakes in me solve the material number essay problem.